EFFECT OF TILT ANGLE ON CURRENT AND POWER CHARACTERISTICS IN PHOTOVOLTAIC MODULE MODEL ET-250 - LUWIS H LAISINA; RINA L MANUHUTU; SYLVIA I PERSULESSY (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2020)
Solar cells or also often called photovoltaics are device with two terminals or connections capable of converting direct sunlight into electricity.which can then be distributed and used for the needs of electrical loads. Solar systems typically use batteries to store excess energy captured during the day for further use at night when there is no sunlight or is used during the day when sunlight radiation is very small, for example when it is dark. or not enough light works like a diode, and when illuminated with sunlight can produce voltage.When illuminated, generally one commercial solar cell produces a dc voltage of 0.5 to 1 volt, and a short-circuit current in milliampere scale per cm2. This large voltage and current is not enough for various applications, so generally a number of solar cells are arranged in series to form solar modules. One solar module typically consists of 28-36 solar cells, and the total produces a dc voltage of 12 V under standard illumination conditions. The current-voltage curve is nonlinear. The greater the load resistance, the closer the load voltage will be to the value of the open connect voltage (Voc) of the solar panel. While the smaller the load resistance, the current flowing into the load will get closer to the short circuit current (Isc) of the solar panel.The power-voltage curve is nonlinear. Solar panel power will be maximum if at the load flows the maximum current (Im) and has a maximum voltage (Vm). The addition of a load that has resistance (R) is smaller than the maximum load resistance, then the power will increase close to the maximum power value (Pm) of the solar panel. While the increase in the load that has resistance (R) is greater than the maximum load resistance, the power will decrease from the maximum power of the solar panel.The longer the cable is used, the maximum power of the solar panels will decrease. The tilt of the solar panels towards the angle comes sunlight affecting the maximum power generated by solar panels.